New nonovershooting step response control for the DC-DC Buck Converter - Schmid, Robert; Cuoghi, S.; Goel, A.; Ntogramatzidis, Lorenzo (IEEE Industrial Electronics Society, 2016)
A key challenge in the control of the DC-DC buck converter is to compensate its lightly damped dynamics, which depend upon the load variations. In this paper we examine the application to DC-DC converter circuits of the linear state feedback tracking control method introduced by Schmid and Ntogramatzidis. This method aims to deliver a time-domain transient response that is both rapid and nonovershooting. The method is tested on a DC-DC buck converter circuit subject to load variations and its transient and robustness performance is compared against that obtained from controllers designed by classical PID methods and also by the feedback posicast method of Hung.